On the necessity and possibilities of providing access for disabled persons to historical public buildings - Rymsza, Barbara; Kaperczak, Krzysztof; Kiljan-Walerzak, Justyna (Protection of Cultural Heritage, 2020)
This publication is dedicated to the problem of providing access to historic public utility buildings for people with disabilities, with simultaneous adaptation of this access to the needs and abilities of disabled persons. It shows examples which show how to provide access to historic buildings to people with disabilities. It also presents the possibility of using the results of a doctoral dissertation concerning the new type of ramp (an LPZ light substitute ramp) characterized by greater "flexibility" of application.